2004
DOI: 10.1128/aac.48.9.3382-3389.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alpha Interferon and Ribavirin on the Function of Maturing Dendritic Cells

Abstract: Alpha interferon and ribavirin are required in combination to achieve a sustained virological response in the treatment of hepatitis C virus (HCV) infection. Alpha interferon has direct antiviral activity and also enhances HCV-specific T-cell responses. Ribavirin has little direct activity against HCV but reduces hepatic inflammation. It is therefore likely that these drugs in combination have hitherto unidentified immunological effects. In the present study we investigated the effects of alpha interferon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 39 publications
4
44
0
2
Order By: Relevance
“…The IL-12-enhancing effect of IFN-α on DCs was corroborated in an independent study where doublestranded RNA was used to induce DC maturation and cytokine production. IFN-α enhanced the production of IL-12 and TNF-α induced by double-stranded RNA but had no effect on IL-10 production [140].…”
Section: V9 Effects Of Type I Interferons On Il-12 Productionmentioning
confidence: 86%
“…The IL-12-enhancing effect of IFN-α on DCs was corroborated in an independent study where doublestranded RNA was used to induce DC maturation and cytokine production. IFN-α enhanced the production of IL-12 and TNF-α induced by double-stranded RNA but had no effect on IL-10 production [140].…”
Section: V9 Effects Of Type I Interferons On Il-12 Productionmentioning
confidence: 86%
“…This was because we were interested in testing patients who had not been previously treated, because IFN-␣ and ribavirin can influence T cell function and also cytokine secretion profiles. 22,36 Additionally, we did not assess the relationship between IL-2 secretion and viral load. A prospective study aiming to look at the IL-2 secretion in more severely affected patients over a range of viral loads is underway, as well as assessing the potential impact of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a is typically used in combination with RBV for treatment of chronic HCV infection (Stark et al, 1998). RBV at physiological doses has no effect on MDC phenotype, whereas IFN-a has been shown consistently to induce MDC maturation (Barnes et al, 2004;Luft et al, 1998). Our results indicated that IFN-a-exposed MDCs from HCV patients acquired a mature phenotype, as defined by the upregulation of HLA-DR and of costimulatory and adhesion molecules, as well as of the maturation marker CD83.…”
Section: R Cicinnati and Othersmentioning
confidence: 99%